Polymerization-induced self-assembly of acrylonitrile via ICAR ATRP - Wang, Guowei; Wang, Zongyu; Lee, Bongjoon; Yuan, Rui; Lu, Zhao; Yan, Jiajun; Pan, Xiangcheng; Song, Yang; Bockstaller, Michael R.; Matyjaszewski, Krzysztof (Polymer (Guilford), 2017)
Polymerization-induced self-assembly (PISA) has attracted growing interest as facile fabrication process of polymer-based nanomaterials. However, PISA of acrylonitrile (AN) by atom transfer radical polymerization (ATRP) has remained an outstanding challenge due to the high activity of AN and poor solubility of polyacrylonitrile (PAN) in AN monomer. Here the application of PISA by using an initiators for continuous activator regeneration (ICAR) ATRP for the synthesis of PAN-based nano-objects is demonstrated. A highly active ATRP macroinitiator, methoxy-poly(ethylene oxide) 2-bromo-2-phenylacetate (mPEO-BPA) was synthesized by esterification and used also as a stabilizer. The molecular weight of the macroinitiator was found to determine the structure of self-assembled nano-objects. The high molecular macroinitiator (mPEO113-BPA) formed nano-objects with spherical or worm-like morphology, while the lower molecular weight analogue (mPEO45-BPA) resulted in precipitation in most cases due to insufficient stabilization of the nano-objects. [Display omitted] •Polymerization-induced self-assembly (PISA) of acrylonitrile (AN) successfully accomplished by atom transfer radical polymerization (ATRP).•Initiators for continuous activator regeneration (ICAR) ATRP with low ppm Cu used for synthesis of PAN-based nano-objects demonstrated.•A highly active ATRP macroinitiator, mPEO-BPA was used as both macroinitiator and stabilizer.•The molecular weight of the macroinitiator determined the structure of self-assembled objects.